Restoration of a Permanent Preservation Area in Tangará da Serra - MT based on Replacement Cost Method - Andrade, Ana Paula Silva de; Correio, Cleci Grzebieluckas (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Brazilian law considers areas around watercourses as Áreas de Preservação Permanente (APP) (Permanent Preservation Areas), which should be restored in case of degradation. This study aimed to present a plant recovery model based on Replacement Cost Method for an 11.7 hectares PPA, near the Water Treatment Station (WTS) of Tangará da Serra - MT. The research presents an applied nature, quantitative approach and structured script as a collection instrument, analyzed through the Replacement Cost Method (RCM), in order to estimate the recovery costs. The environmental diagnosis of the area showed the need for densified planting, at an estimated cost of R$ 24,492.00, with the greatest cost impact concentrated in implementation phase.